2022
DOI: 10.3390/ijerph19031892
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heating on Physicochemical Property of Aerosols during Vaping

Abstract: Many electronic cigarette manufacturers have offered different types of “high-end mods” that allow for controlled heating of the e-liquid. However, the controlled heating condition can drastically alter the inhaled aerosols’ physical properties and chemical substances, causing potential health risks. To investigate the contribution of heating on aerosol properties, we used four common power settings in the mods to conduct a physicochemical analysis. Our data showed that the aerosol mass and nicotine content in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Various studies have showed particle mass emissions that increased with higher power because of larger PG/VG mass consumption [ 25 , 47 , 54 , 55 ], which is consistent with the overall trend in this study that a 0.2 Ω coil emitted higher particles than a 0.6 Ω coil. However, for the same coil resistance, an increase in power seemed to have no effect or a decreasing trend on particle emissions.…”
Section: Discussion and Limitationssupporting
confidence: 91%
“…Various studies have showed particle mass emissions that increased with higher power because of larger PG/VG mass consumption [ 25 , 47 , 54 , 55 ], which is consistent with the overall trend in this study that a 0.2 Ω coil emitted higher particles than a 0.6 Ω coil. However, for the same coil resistance, an increase in power seemed to have no effect or a decreasing trend on particle emissions.…”
Section: Discussion and Limitationssupporting
confidence: 91%
“…The nicotine levels in e-cigarette aerosols are influenced by factors such as the nicotine concentration in the e-liquid, the PG/VG ratio, the power of the e-cigarette, the heating temperature, and puff topography. 36,37 In this study, only the nicotine concentration in the e-liquids was changed, leading to the observed result of the linear relationship. Additionally, the results obtained by SMPS and GC-FID demonstrate that the nicotine levels are the only variables changing within these aerosols, making them excellent calibration sources and expanding the calibration range easily.…”
Section: Resultsmentioning
confidence: 78%
“…According to recent research, the aerosolized e-liquid emitted from a heated ENDS may have physicochemical properties similar to those of high-sucrose gelatinous confectionery and acidic drinks. The viscosity of e-liquids combined with the chemicals in the flavorings may therein increase the risk of dental caries ( 53 ).…”
Section: Discussionmentioning
confidence: 99%